Synthesis of Enantioenriched Indolines by a Conjugate Addition/Asymmetric Protonation/Aza-Prins Cascade Reaction - Daniels, Blake E. (Angew Chem Int Ed Engl, 2016)
A conjugate addition/asymmetric protonation/aza-Prins cascade reaction has been developed for the enantioselective synthesis of fused polycyclic indolines. A catalyst system generated from ZrCl(4) and 3,3’-dibromo-BINOL enables the synthesis of a range of polycyclic indolines in good yields and high enantioselectivity. A key finding is the use of TMSCl and 2,6-dibromophenol as a stoichiometric source of HCl to facilitate catalyst turnover. This transformation is the first in which a ZrCl(4)•BINOL complex serves as a chiral Lewis acid-assisted Brønsted acid.